2012
DOI: 10.1016/j.visres.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heterophoria type and myopia on accommodative and vergence responses during sustained near activity in children

Abstract: The influence of phoria-type and myopia on changes to vergence and accommodation during prolonged near-task was examined in 53 children. Participants were classified into phoria and refractive categories based on near phoria and cycloplegic refraction respectively. Measures of near phoria, binocular (BA) and monocular accommodation (MA) were obtained before and during a 20 min task when children binocularly fixated a high-contrast target at 33 cm through best corrective lenses. Vergence adaptation and accommod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 70 publications
2
32
0
3
Order By: Relevance
“…In the Tassinari study, mean lags with MEM retinoscopy were 0.23 D for exophoria, 0.32 D for orthophoria and 0.49 D for esophoria. The results of the present study are also consistent with the findings of Sreenivasan, Irving and Bobier that the accommodative response increases from monocular to binocular conditions in persons with higher than normal exophoria and that accommodative response decreases from monocular to binocular viewing in esophoria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the Tassinari study, mean lags with MEM retinoscopy were 0.23 D for exophoria, 0.32 D for orthophoria and 0.49 D for esophoria. The results of the present study are also consistent with the findings of Sreenivasan, Irving and Bobier that the accommodative response increases from monocular to binocular conditions in persons with higher than normal exophoria and that accommodative response decreases from monocular to binocular viewing in esophoria.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, participants with exophoria at near‐point may have a higher accommodative response binocularly than monocularly because they accommodate more when they converge to fuse. Such findings were reported by Sreenivasan, Irving and Bobier . They found that participants with more than six prism dioptres of exophoria at near‐point had an increase in accommodative response going from monocular to binocular conditions and participants with more than two prism dioptres of esophoria at near‐point had a decrease in accommodative response going from monocular to binocular conditions.…”
supporting
confidence: 79%
“…Several studies agreed that the onset and progression of myopia is associated esophoria at near12132728 and with a higher degree of myopia 29. In Leone et al’s11 study, more 6-year-old children presented with lower myopia than those aged 12 years, and they found the significant association between myopia and near heterophoria.…”
Section: Discussionmentioning
confidence: 94%
“…Calibration procedures followed for the PowerRefractor were similar to those described in 114 previous studies (Sreenivasan, Irving, & Bobier, 2012, 2014. Gradient response AC/A 115 (Accommodative convergence per diopter of accommodative response) was quantified as the 116 change in the phoria with negative lenses.…”
Section: Accommodative Parameters 111mentioning
confidence: 99%